2001
DOI: 10.1161/01.cir.103.13.1740
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Neointimal Thickness and Shear Stress After Wallstent Implantation in Human Coronary Arteries

Abstract: Background-In-stent restenosis by excessive intimal hyperplasia reduces the long-term clinical efficacy of coronary stents. Because shear stress (SS) is related to plaque growth in atherosclerosis, we investigated whether variations in SS distribution are related to variations in neointima formation. Methods and Results-In 14 patients, at 6-month follow-up after coronary Wallstent implantation, 3D stent and vessel reconstruction was performed with a combined angiographic and intravascular ultrasound technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
221
0
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(236 citation statements)
references
References 36 publications
(36 reference statements)
7
221
0
8
Order By: Relevance
“…5,6 The poststent FFR detects a residual pressure gradient across the stented and adjacent segments that can play an important role in restenosis. 8,14 Although the validation of FFR for the purpose of the assessment of optimal bare metal stent deployment was reported, 5,8 to our knowledge, few reports on its use in the context of DESs have been published. In the present study, several intuitive findings were observed according to the FFR range after stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The poststent FFR detects a residual pressure gradient across the stented and adjacent segments that can play an important role in restenosis. 8,14 Although the validation of FFR for the purpose of the assessment of optimal bare metal stent deployment was reported, 5,8 to our knowledge, few reports on its use in the context of DESs have been published. In the present study, several intuitive findings were observed according to the FFR range after stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Following coronary stent deployment, sites of aggressive neointimal hyperplasia also correspond to sites subjected to non-physiological flow conditions, and this has been attributed to increased endothelial dysfunction and permeability. 6,17,18,20,21,52,71,79,88 The hemodynamic impact of the investigated stents was evaluated in terms of the relative residence time distribution predicted upon the lumen surface during the third cardiac cycle. The RRT accounts for temporal variations in both the magnitude and the orientation of the instantaneous wall shear stress vector and is calculated as follows:…”
Section: Analysis Of Balloon-expandable Coronary Stentsmentioning
confidence: 99%
“…6,17,18,20,21,52,71,79,88 In light of these observations, a significant body of research has been carried out in this area. Due to the difficulty involved in the evaluation of these phenomena in an in vivo setting however, a large portion of this research has been carried out using computational methods of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition to conventional risk factors for stent restenosis, the restored level of blood flow seems to be a crucial factor in the development of neointimal hyperplasia (NH). 3 It has been postulated that wall shear stress (WSS) is an important causative factor. Indeed, other studies 4 have demonstrated that low WSS is associated with and even predicts NH in either bypass graft or stents.…”
mentioning
confidence: 99%